Science and Theology - Chethimattam, John B (Journal of Dharma, 1983)
Science and Religion, and much more Science and Theology sound as strange combinations. They belong to radically different areas and levels of human knowledge, one dealing with the intimate and transcendental area of faith and the other dealing with the mundane empirical world. Even in the heyday of scholasticism under the tutelage of the Church, theology was a minority faculty in universities, the big majority of students opting for the arts and science faculties. There was a climate in Western universities in the recent past in which religion and theology were considered an aberration of human reason, lacking the precision and clarity of the empirical sciences, often grouped with myth, magic and folklore. But today the study of religion and even of Christian theology has gained a certain prestige and standing in the universities.